The modulatory mechanism of spatial distance on the role of internal attention in unattended working memory representations. - Liu, Qiang; Guo, Lijing; Wang, Jie; Nie, Dan; Ye, Chaoxiong (Visual Cognition, 2024)
Visual working memory (VWM) temporarily stores visual information, supporting higher cognition. Internal attention selectively prioritizes VWM representations, influencing both cued and uncued items. This study examined how spatial distance modulates internal attention's effect on unattended representations. Two experiments using a lateralized change detection task assessed retro-cue effects. Experiment 1 revealed that uncued items closer to the cued item exhibited less memory decline, supporting an attentional spatial proximity effect. Experiment 2, with reduced memory load and controlled spatial configurations, confirmed that proximity to the cued item mitigates memory loss, independent of intervening items. Moreover, increasing spatial distance gradually reduced VWM performance, reinforcing a graded attentional effect. These findings indicate that internal attention extends its benefits beyond the cued representation, illuminating how spatial distance helps manage limited VWM capacity. Overall, this work advances our understanding of the flexible and spatially sensitive mechanisms governing attentional processes in VWM.